RISIKO KAWASAN KONSERVASI SEBAGAI OBJEK WISATA (STUDI KASUS KAWASAN KONSERVASI PENYU KOTA PARIAMAN) - Irfan Bifthaussalam; Siti Sofro Sidiq (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Conservation is the concept of the process of managing a place, space or object so that the cultural meaning contained therein is well preserved. Activities in a conservation itself include all maintenance activities in accordance with local conditions and situations as well as development efforts for further use. Ecotourism is currently experiencing development in Indonesia. Many regions in Indonesia have started to develop ecotourism, one of which is Kota Pariaman. Pariaman City is a city that is developing ecotourism, one of the Turtle conservation. The following are the phenomena of problems the writer found in Apar Village, Kota Pariaman, namely (1) the turtle conservation area has caused various dynamics for the community, namely environmental changes and socio-cultural changes. In facing changes, the community adapts according to their knowledge. (2) The development of a turtle conservation ecotourism area has caused conflict between the Pariaman City Government and the Apar Village community. (3) The problem of the need for veterinarians to handle sick turtles in captivity is still limited. Problem formulation is the risk of turtle conservation areas as a tourism object. And Risk Management in the Turtle Conservation Area of Kota Pariaman. This type of research is a qualitative descriptive study. Data collection techniques, namely interviews, observation, and documentation. Data analysis techniques used in qualitative research include transcripts of interview results, data reduction, analysis, data interpretation and triangulation. Risk Identification of the Kota Pariaman Turtle Conservation Area is Identification Focused on Where Business Operators in the Tourism Industry Conduct Their Business Operations, Identification Is Addressed to Basic Parameters and Boundaries Determined to Identify Risks That Must Be Managed, and Risk Management in the Turtle Conservation Tourism Object Area Pariaman City.Key words : Conservation, Identification of Risk, Ecotourism